2002
DOI: 10.1021/ma0212947
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Studies of pH-Responsive Unimolecular Micelles Formed from Amphiphilic Polysulfonates Possessing Long-Chain Alkyl Carboxyl Pendants

Abstract: Reversible pH-induced changes in self-associative behavior in water of random copolymers of 50 mol % sodium 2-(acrylamido)-2-methylpropanesulfonate (NaAMPS) and 50 mol % 6-acrylamidohexanoic acid (AmH), 8-acrylamidooctanoic acid (AmO), or 11-acrylamidoundecanoic acid (AmU) were investigated by various fluorescence techniques with use of fluorescence-labeled polymers. Fluorescence intensities, lifetimes, depolarization, and quenching for the polymers labeled with naphthalene (4 mol %) indicated that all the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 37 publications
2
54
1
Order By: Relevance
“…8 shows the size distribution and average size of the polymer colloids, i.e., unimolecular micelles, formed by poly (NaAMPS-co-NaMmO) and poly(NaAMPS-co-NaMmD) at pH 6. The average size of the polymer colloids observed in this study was 7-12 nm, and was similar to that of the unimolecular micelles reported by Yusa et al [14], although the size distribution was quite wide. Furthermore, the polymer colloids formed by poly (NaAMPS-co-NaMmO) were larger than those formed by poly (NaAMPS-co-NaMmD), although the side chain of NaMmO is shorter than that of NaMmD.…”
Section: Protonation Of Poly(naamps-co-nammh) and Poly(naamps-conammo)supporting
confidence: 90%
See 2 more Smart Citations
“…8 shows the size distribution and average size of the polymer colloids, i.e., unimolecular micelles, formed by poly (NaAMPS-co-NaMmO) and poly(NaAMPS-co-NaMmD) at pH 6. The average size of the polymer colloids observed in this study was 7-12 nm, and was similar to that of the unimolecular micelles reported by Yusa et al [14], although the size distribution was quite wide. Furthermore, the polymer colloids formed by poly (NaAMPS-co-NaMmO) were larger than those formed by poly (NaAMPS-co-NaMmD), although the side chain of NaMmO is shorter than that of NaMmD.…”
Section: Protonation Of Poly(naamps-co-nammh) and Poly(naamps-conammo)supporting
confidence: 90%
“…Poly(NaAMPSco-NaAmO), poly(NaAMPS-co-NaAmU), and poly(NaAMPS-coNaMmD) form unimolecular micelles at pH ranges of 6-7, 7-8, and 9-10, respectively [14,17]. This implies that the pH at which the unimolecular micelles are formed can be controlled by the length of the hydrophobic components, i.e., the number of methylene groups in the pendant hydrophobic group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we selected poly(1-ethynylpyrene) as model molecule because the pyrene unit is an efficient fluorescent probe, which has been successfully used as a molecular label in the study of many polymers [21][22][23][24][25][26][27][28][29][30]. It is well known that pyrene has a long singlet lifetime and that it readily forms excimers; the relevant photophysical properties of pyrene have recently been reviewed [31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have studied the thermal, optical, electrochemical properties and conductivity of polyarylacetylenes bearing condensed aromatic groups in function of the geometry of the polyacetylene backbone and the internal stacking of pendant substituents [13,14]. For this purpose, we selected poly(EP) as model molecule because pyrene is an efficient fluorescent probe, which has been successfully used as a molecular label in the study of a huge variety of polymers [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%